Sulfated polysaccharide from the marine algae Hypnea musciformis inhibits TNBS-induced intestinal damage in rats. (20th October 2016) - V. Brito, Tarcisio; Barros, Francisco C.N.; Silva, Renan O.; Dias Júnior, Genilson J.; C. Júnior, José Simião; Franco, Álvaro X.; Soares, Pedro M.G.; Chaves, Luciano S.; Abreu, Clara M.W.S.; de Paula, Regina C.M.; Souza, Marcellus H.L.P.; Freitas, Ana Lúcia P.; et al.
Highlights: Polysaccharides (PLS) significantly reduced the inflammatory response during colitis induced by TNBS. PLS reduced the neutrophil migration and decreased the cytokine level on colonic tissue. Pre-treatment of rats with PLS significantly reduced the oxidative stress and damage on the intestinal tract. Abstract: Sulfated polysaccharides extracted from seaweed have important pharmacological properties. Thus, the aim of this study was to characterize the sulfated polysaccharide (PLS) from the algae Hypnea musciformis and evaluate its protective effect in colitis induced by trinitrobenzene sulfonic acid in rats. The sulfated polysaccharide possess a high molecular mass (1.24 × 10 5 g mol −1 ) and is composed of a κ-carrageenan, as depicted by FT-IR and NMR spectroscopic data. PLS was administered orally (10, 30, and 60 mg/kg, p.o.) for three days, starting before TNBS (trinitrobenzene sulfonic acid) instillation (day 1). The rats were killed on day three, the portion of distal colon (5 cm) was excised and evaluated macroscopic scores and wet weight. Then, samples of the intestinal were used for histological evaluation and quantification of glutathione, malonyldialdehyde acid, myeloperoxidase, nitrate/nitrite and cytokines. Our results demonstrate that PLS reduced the colitis and all analyzed biochemical parameters. Thus, we concluded that the PLS extracted from the marine algae H. musciformis reduced the colitis in animal model and may have an important promising application in the inflammatory bowel diseases.